2020
DOI: 10.1155/2020/8757281
|View full text |Cite
|
Sign up to set email alerts
|

Early Learning Curve in the Assessment of Deep Pelvic Endometriosis for Ultrasound and Magnetic Resonance Imaging

Abstract: Purpose. We aimed to compare the learning curves of an ultrasound trainee (obstetrics and gynecology resident) and a radiology trainee when assessing pelvic endometriosis. Methods. Consecutive patients with suspected endometriosis were prospectively enrolled in a tertiary center. They underwent an ultrasound and magnetic resonance imaging preoperatively, which was reported according to the International Deep Endometriosis Analysis (IDEA) group consensus. Trainees reported on deep endometriosis (DE), endometrio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Kelly et al ( 2020 ) showed that, when comparing ultrasound and MRI learning curves for diagnosis of DE, ultrasound trainees had positive learning curves in more anatomical locations (bladder, adenomyosis, overall bowel DE, frozen pelvis) than the radiology/MRI trainees (bladder, adenomyosis). This may indicate that when assessing bowel DE, the learning curve for ultrasound is faster compared to the learning curve for MRI.…”
Section: Discussionmentioning
confidence: 99%
“…Kelly et al ( 2020 ) showed that, when comparing ultrasound and MRI learning curves for diagnosis of DE, ultrasound trainees had positive learning curves in more anatomical locations (bladder, adenomyosis, overall bowel DE, frozen pelvis) than the radiology/MRI trainees (bladder, adenomyosis). This may indicate that when assessing bowel DE, the learning curve for ultrasound is faster compared to the learning curve for MRI.…”
Section: Discussionmentioning
confidence: 99%
“…In order to explore a possible learning curve, the older adults were divided over three sets of participants based on the chronological order of the first ultrasound measurement occasion [ 48 ]. The SEM for each morphology measure was calculated for each set of participants.…”
Section: Methodsmentioning
confidence: 99%
“…Videoclips were downloaded in Mp4 format from the hospital electronic database system and then de-identi ed prior to get reanalyzed by three intermediate ultrasound skilled trainees. These trainees were 4th year residents in O&G with intermediate ultrasound skills (consisting of more than 500 gynecologic ultrasound cases) doing their postgraduate studies in endometriosis management [27]. The trainees blinded to clinical data were asked separately to make their own diagnosis reviewing uterine images of testing set.…”
Section: Diagnostic Performance Of Traineesmentioning
confidence: 99%
“…The development of standardized and shared diagnostic criteria for the ultrasound diagnosis of adenomyosis has made it possible to achieve adequate levels of accuracy (around 83%), but only in the hands of experienced sonographers or after an intensive and supervised training of O&G trainees [9,27].…”
Section: Main and Interpretationmentioning
confidence: 99%